Argan oil and the question of empowerment in rural Morocco. - Perry, Wendy; Rappe, Olivia; Boulhaoua, Ali; Hassan Loux, Latifa; Elhouss, Youness; Ait Ahssain, Hichame; Ait Barich, Zohra; Akhiyat, Hasna; Aznague, Tayeb Amine; Hraïd, Sahar (Journal of North African Studies, 2019)
Morocco's international development enterprise, the National Initiative for Human Development (INDH), aims to boost the economy and stimulate the integration of marginalised groups, including rural women. Has the INDH achieved social impact? Are attitudes changing toward women's economic independence, literacy, numeracy, political participation, and overall freer participation in a society that has long disadvantaged women? This mixed-methods approach to impact evaluation compares rural women's and men's views toward democratisation and women's empowerment in developing communities where INDH-supported argan oil cooperatives exist and in similar, undeveloped communities where they do not. Using two survey instruments tailored to women and men, the American-Moroccan research team collected quantitative and qualitative data through 829 surveys with randomly selected, overwhelmingly Amazigh (Berber) participants in fifty-four communities in the Atlas Mountains and their foothills. Results reveal the core tension of the INDH mission. While the impact of these programmes, or treatment, is clearer on women than on men—the men being profoundly conflicted—positive correlations exist between treatment and women earning money and viewing opportunity in their communities. At the same time, in some regards treatment adversely correlates to greater gender parity, and in crucial ways other variables, such as basic math skills, more strongly predict favourable attitudes than treatment. In effect, rather than transforming society, these INDH-funded programmes strengthen the state's stability and control, giving just enough help to rural women to have a modest positive impact without eroding the bedrock of traditional rural society, which the argan tree poetically symbolises for Moroccans.